PROSTHODONTIC REHABILITATION OF A PATIENT WITH ORAL SUBMUCOUS FIBROSIS AND MICROSTOMIA : A CASE REPORT - D., Anupama Prasad; D., Krishna Prasad; Hegde, Chethan (Journal of Health and Allied Sciences NU, 2012)
This case report deals with treatment of a female patient aged 45 years with limited mouth opening due to submucous fibrosis ,who was completely edentulous and was prosthetically treated with modification of techniques for impression making and jaw relation so that a complete denture was made without sections which could be easily inserted and removed without compromising retention and esthetics.
Keywords: limited mouth opening; oral submucous fibrosis; sectional trays; microstomia